MEANS OF IMPROVING THE QUALITY OF SERVICE OF THE COMPUTER NETWORK OF THE FORENSIC INFORMATION SYSTEM - Mykhailo Mozhaiev; Oksana Melashchenko; Viktoria Roh; Maksym Usatenko (Сучасний стан наукових досліджень та технологій в промисловості, 2020)
The relevance of research. In modern forensic practice, computer networks (CN) are an integral part of computer-technical examination, therefore, ensuring their normal functioning becomes a vitally important task. In this regard, the theory of the construction, modification and operation of digital telecommunication systems raises a fairly general problem of digital signal processing, network synchronization and its stability. A solution to this problem was devoted to research, which analyzed the characteristics of the stability of the network and proposed methods for measuring the physical parameters that determine it.  Many of the studies conducted were based on the use of frequency measurements in communication channels of computer networks for transmitting information. Acousto-optic spectrum analyzers (AOSAs) are widely used in forensic information system networks improving the QoS of forensic computer networks. The subject of the research: resolution of acousto-optical spectrum analyzers. The purpose of the research to improve the quality of diagnostics of parameters of computer information transmission networks based on the use of the developed signal processing technique in acousto-optic spectrum analyzers, which allows increasing the resolution of AOSA by increasing the frequency resolution of two non-simultaneous long-duration radio pulses. The results of the research. The research presents analysis of the influence of the frequency parameters of the computer network on the implementation of the relevant requirements for quality of service. Studies have been carried out on possible ways to increase the resolution of AOAC in frequency. The nonlinear characteristics of AOSA were studied, which made it possible to modernize methods for increasing the frequency resolution. The classical method of processing radar signals is used, which allows determining the delay time of arrival of a sufficiently long pulse with an accuracy significantly exceeding the pulse size. When analyzing the operation of AOSA, it is taken into account that the signal photoelectron flux in the acousto-optical spectrum analyzer is known to be described by the Poisson distribution. But one of the main properties of random variables distributed according to Poisson's law is the lack of cross-correlation of the components of the Poisson stream. This assumption can significantly increase the frequency resolution of AOSA. Conclusions. The research ascertains analytical relationship for the dispersion of the signal frequency measurement. The research proposes a technique for processing signals in AOSA, allowing to increase the resolution of AOSA by increasing the frequency resolution of two non-simultaneous radio pulses of long duration.